ACCOUNTANTS' LIABILITY TO THIRD PARTIES: THE ULTRAMARES CASE REAFFIRMED. - Brady, William W. (The Accounting Review, 1938)
Abstract On May 28, 1938 in the case of State Street Trust Co. v. Ernst, (15 N.E. (2d) 416), the New York Court of Appeals reaffirmed the major principles of the Ultramares case. In an action against the accountants by third parties not contracting with the accountants (the plaintiff bank made a loan on the basis of the certified statement), the court held that the question of liability could go to the jury on an issue of fraud as to whether the accountants had a bonafide belief in the truthfulness of their certificate. The Ultramares case precluded liability of accountants to third parties on grounds of negligence, but it declared that there could be liability if a jury could find a reckless misstatement, or an opinion based on grounds so flimsy as to lead to the conclusion that there was no genuine belief in its truthfulness. That is, gross negligence could establish liability when mere negligence would not. The nature of the action would be in fraud, and the flimsy grounds stated above would take the place of actual intent to deceive. The right to sue would extend to all who relied on the certificate and whom the accountants might reasonably expect would be making such reliance.